Developing and validating a social model for xenophobic violence in South Africa - Crawley, Kieron (My University, 2014)
Widespread outbreaks of xenophobic violence within informal urban settlements is a recent feature of South African Society that has troubled politicians and challenged social analysts. While the number of “episodes” has been limited, such has been their ferocity that in 2008 they garnered huge media attention both at home and abroad. The potential to shatter the image of the “rainbow nation” and to compromise the post apartheid nation-building project has not been lost on Government, who along with political scientists and sociologists are keen to build a better understanding of “what is going on”1. This study re-examines the dynamics surrounding xenophobic episodes in an attempt to make sense of the range of social theorem that have been put forward by analysts and commentators to explain the phenomenon. Drawing specifically upon Relative Deprivation Theory and looking closely at the dynamics of social rank and access to opportunity – the study explores a hypothetical framework that suggests the critical role of opportunity shock in transforming a volatile environment for xenophobia into a potentially explosive one. The main body of the report sets out feedback and analyses of the model arising from interviews with recognised experts, while a discussion section of the report uses concepts and ideas that have emerged from conversation to set out a number of areas that would seem to warrant more investigation in the research of this troubling social phenomenon.
MM (P&DM) thesis
Keywords: Xenophobia